Case report: Clinicopathological characteristic of two cases of primary endometrial squamous cell carcinoma and review of the literature - Zhang, Hui-Bin; Lin, Li-Hua; Lin, Qiu-Ping; Lin, Yuan-Qing; Luo, Dan; Xu, Shu-Xia (Frontiers in Oncology, 2024)
Primary endometrial squamous cell carcinoma (PESCC) is a rare malignant tumor. To investigate the clinical and pathological features of PESCC, two cases of PESCC in Fujian Maternal and Child Health Hospital were retrospectively studied and the literatures were reviewed. Both of the two cases were menopausal women aged 57–62 years, clinically presenting with “vaginal discharge”. Case 1 was a non-keratinising squamous cell carcinoma with high-risk HPV infection. Tumor infiltrated in deep myometrium with multifocal intravascular thrombus and macro metastases to one pelvic lymph node (1/15) and abdominal aortic lymph node (1/1). Lung metastasis occurred 36 months after the surgery. After surgical resection and without postoperative supplemental therapy, the patient remained tumor-free for 110 months to date. Case 2 had a history of breast cancer for 5 years and long-term intake of aromatase inhibitor drugs without HPV infection. It was a keratinized squamous cell carcinoma. Tumor also infiltrated in deep myometrium with multifocal intravascular thrombus and one pelvic lymph node metastasis (1/18), However, no metastasis was seen elsewhere. To date, the patient survived for 16 months without tumor after surgery. Both of the two cases expressed squamous epithelial markers P40, P63, and CK5/6, but neither expressed PAX8 or PR. Case 1 had diffuse expression of P16, wild-type P53, and ER-negative. Case 2 had negative P16, mutant P53, and focal positive ER. PESCC is often associated with HPV infection and low estrogen levels. However, studies in the literatures have found that P16 expression is not always consistent with HPV infection, indicating that PESCC cannot be easily classified as HPV-associated or non-dependent like cervical cancer. There are two main patterns of P16 and P53 expression, P16-positive/P53 wild-type and P16-negative/P53-mutant, but no positive expression of both has been seen so far. It is worth noting that we reported the second case of PESCC with a history of breast cancer, where the patient had been taking the oral aromatase inhibitor drug (exemestane) for a long period of time to reduce the estrogen level, indicating the low estrogen level may be also a key factor in the pathogenesis of PESCC.